Gestión del conocimiento y su incidencia en la eficiencia y economía del instituto ecuatoriano de capacitación empresarial IECE. plan de capacitación virtual - Cerezo Bustamante, Carmen Meribet (2021)
The present investigation was carried out in the Ecuadorian Institute of Business Training "IECE", located in the Quevedo canton, via Quito km 1/12 via Santo Domingo. Faced with the detected problem, the general objective was to evaluate the incidence of knowledge management in the efficiency and economy of the Ecuadorian Institute of Business Training IECE. The theoretical framework was structured in three parts, each conceptual, theoretical and legal foundation with its corresponding citations and bibliography. To meet the stated objectives, a qualitative-quantitative approach was maintained, and deductive, inductive and descriptive methods were used. For the collection of information, it was necessary to resort to techniques such as the survey and interview that was carried out with the collaborators and the owner of the company respectively. As a result of the investigation, it was identified that one of the main needs presented by the Ecuadorian Institute of Business Training is related to the transmission and updating of knowledge of the collaborators since the company does not have a formal training plan that promotes the generation of information and innovation, leaving as an effect deficiencies that influence the efficiency and economy of the company.